2023
DOI: 10.3390/microorganisms11020513
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Types of LAB on Dynamic Fermentation Quality and Microbial Community of Native Grass Silage during Anaerobic Fermentation and Aerobic Exposure

Abstract: Silage of native grasses can alleviate seasonal forage supply imbalance in pastures and provide additional sources to meet forage demand. The study aimed to investigate the effects of Lactobacillus plantarum (LP), Lactobacillus buchneri (LB), and Lactobacillus plantarum in combination with Lactobacillus buchneri (PB) on the nutritional quality, fermentation quality, and microbial community of native grass silage at 2, 7, 15, and 60 days after ensiling and at 4 and 8 days after aerobic exposure. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 75 publications
0
0
0
Order By: Relevance
“…At the phylum level, the dominant phyla in the mixed silage of king grass and rice straw were Firmicutes and Proteobacteria, which aligned with the findings in previous studies ( Liu M. et al, 2022 ; Zhang et al, 2023 ). The phylum Firmicutes contains numerous lactic acid bacteria that are actively involved in the process of fermentation, which plays a crucial role in the production of lactic acid during the later stage of ensiling ( Zhao et al, 2017 ).…”
Section: Discussionsupporting
confidence: 90%
“…At the phylum level, the dominant phyla in the mixed silage of king grass and rice straw were Firmicutes and Proteobacteria, which aligned with the findings in previous studies ( Liu M. et al, 2022 ; Zhang et al, 2023 ). The phylum Firmicutes contains numerous lactic acid bacteria that are actively involved in the process of fermentation, which plays a crucial role in the production of lactic acid during the later stage of ensiling ( Zhao et al, 2017 ).…”
Section: Discussionsupporting
confidence: 90%
“…There is evidence that the LAB treatments performed in mixed form produce higher LA and significantly reduce unwanted microbes in comparison with single strain treatments. In addition, a LAB co-culture treatment extends the fermented silage storage time while preserving nutrients [13,18,19,32]. Considering the observations above, whole-crop triticale silage was produced under different moisture conditions in the presence of different LAB strains, using either single or co-culture treatments, for 180 and 360 days.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that lactic acid bacteria (LAB) inoculants affect the silage microbiology by increasing the abundance of specific bacteria over others [20,[31][32][33]. For example, the increase in abundance of Limosilactobacillus and Lentilactobacillus bacterial genera have been reported for silages treated with LAB inoculants during ensiling [20,[33][34][35]. These changes in silage bacterial composition are associated with the improved quality [33,35,36] and aerobic stability of open silage [20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the increase in abundance of Limosilactobacillus and Lentilactobacillus bacterial genera have been reported for silages treated with LAB inoculants during ensiling [20,[33][34][35]. These changes in silage bacterial composition are associated with the improved quality [33,35,36] and aerobic stability of open silage [20]. The manipulation of the silage microorganisms' compositional structure is critical for improving the silage quality and nutrient-use efficiency [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation